Infusing Anarchist Pedagogy into Counselor Education - Andrew Wood (Teaching and Supervision in Counseling, 2023)
Anarchist pedagogy has existed for well over 100 years, but little has been written on the subject within the counseling profession and the counselor education literature specifically. Anarchist pedagogy offers a direct relationship between education and social justice praxis that many counseling programs espouse, and thus the consideration of an explicitly political pedagogy may benefit the counselor education profession. This manuscript aims to provide a brief overview of anarchist pedagogy, how it fits into the work of counselor education, and how counselor educators can utilize anarchist pedagogy. Limitations for the infusion of anarchist pedagogy into counselor education and future areas of research are detailed.
Keywords: anarchism; pedagogy; counseling; counselor education